Integrated crop-livestock systems in semiarid regions improve sheep performance compared to traditional use of natural rangelands: Nutrient digestibility, biochemical parameters, microbial protein and carcass traits - Claudenilde de Jesus Pinheiro Costa; Jheiny Rafaela Carvalho Lima; Rodrigo Barbosa de Medeiros; Maria Luana Medeiros; Arthur Lucas Julio Silva; Anderson da Silva Sales Torres; Thaysa Rodrigues Torres; Francisco Fernando Ramos de Carvalho; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos; José Carlos Batista Dubeux; Evaristo Jorge Oliveira de Souza (Small Ruminant Research, 2026)

Metabolic response to anthelmintic treatment in beef cattle with subclinical gastrointestinal nematode infection - Mateus Lotério Coelho; Bianca Thais Baumann; Arthur Souza Galvão; Márcia Rocha Vicente; Murilo Damasceno Brunet De Freitas; Breno Braga Barros; Daniel de Castro Rodrigues; Siddartha Torres Rico; Eduardo Dos Santos; Nara Cônsolo; Luiz Colnago; Fernanda Ocampos; et al. (Veterinary Parasitology, 2026)

Microplastics and warming: dual threats to planktonic protist communities in freshwater ecosystems - Matheus Henrique de Oliveira de Matos; João Vitor Bredariol; Yasmin Rodrigues de Souza; João Vitor Fonseca da Silva; Vinícius Marcelo Souza Castro; Felipe Morais Zanon; Loiani Oliveira Santana; Gabriel Arthur Lopes da Silva; Juliana Regina Kloss; Thomaz Aurélio Pagioro; Luiz Felipe Machado Velho (Hydrobiologia, 2026)

Vinasse fertigation modifies soil–microbiota–plant interactions and metabolism in sugarcane - Arthur César Monico; Adriana Barboza Alves; Mariana Vitória Silvério Alves; Wisley Moreira Farias; Lúcia Pinheiro Santos Pimenta; Elizabeth Luciana Marinho Miguel; Gustavo Henrique Gravatim da Costa; Heytor Lemos Martins; Osania Emerenciano Ferreira; Alan Rodrigues Teixeira Machado; Eduardo da Silva Martins (Chemosphere, 2026)

Droplet class and spray volume influence on spray characteristics and herbicide performance in a maize-Brachiaria grass intercropping system - Arthur Duarte Rodrigues Neto; Thais Regina Ramos Alves; Leandro Tropaldi; Daniel Nicodemo; Fernando Shintate Galindo; Paulo Humberto Pagliari; Ronaldo Cintra Lima; Vagner do Nascimento; Marina Funichello; Evandro Pereira Prado (Phytoparasitica, 2026)
Optimizing maize–Brachiaria intercropping requires effective weed management with selective maize herbicides. This study evaluated the spray performance and efficacy of atrazine + nicosulfuron for weed management in maize–Brachiaria intercropping, focusing on how droplet classes and spray volumes affect maize growth and yield. The deposition experiment was conducted in a greenhouse in a completely randomized design with six replications. Field experiments were conducted during two seasons [2021 early season—ES (rainy season) and 2022 late season—LS (dry season) in a randomized block design and a 4 × 2 factorial (fine, medium, coarse, and very coarse droplet classes × spray volumes of 77 and 144 L ha −1 ) plus four controls treatments: Maize + Brachiaria without weed control, Maize + Brachiaria manually weeding, Brachiaria manually weeding, and Maize manually weeding. The study revealed that droplet class and spray volume significantly influence droplet deposition. Treatments spraying fine droplets at 144 L ha −1 exhibited higher coverage and droplet density levels. Intercropping maize with Brachiaria grass can be achieved without significant yield losses in the ES. However, the intercropping system reduced maize yield by approximately 17% in the LS. Applying the herbicides atrazine + nicosulfuron at 144 L ha −1 improved weed control and positively impacted maize yield during the LS.

Meta-analysis of woody plant diversity and aboveground biomass stock co-benefits across Amazon agroforestry systems - Thamires Campos de Almeida; Silvio Nolasco de Oliveira Neto; Arthur da Cruz Silva; Rodrigo Gomes Gorsani; Lorena Evangelista Fernandes; Sebastião Venâncio Martins; Mehdi Heydari; Andrés Iván Prato; Lisandra Mendes Louzada-Camilo; Ana Luiza Rangel; Jamerson Souza da Costa; Alisson Lopes Rodrigues; et al. (Agroforestry Systems, 2026)

Using the capabilities approach to achieve people‐centered conservation - Arthur Rodrigues; Felipe P. L. Melo; Lucas Alencar; James Angus Fraser; Luke Parry (Conservation Biology, 2026)
Top‐down interventions carried out by state and nonstate institutions to conserve biodiversity and improve the lives of forest‐proximate people (FPP) in the Global South tend to reflect economistic understandings of human well‐being. More progressive and people‐centered conservation projects are guided by normative visions of how the world should be, yet these projects are limited because the social dimensions of project design, planning, and evaluation often remain focused on quantifiable aspects of well‐being. We demonstrated that considering human well‐being qualitatively in terms of freedom and dignity can help achieve rights‐based, people‐centered conservation. We applied the capabilities approach (CA), a social theory that emphasizes marginalized people's freedom to live a life they have reason to value. First, we reviewed English‐language literature to assess how the CA has been used conceptually and empirically to examine the well‐being of FPP. Based on 31 methodologically diverse studies from 16 countries, we found that equitable access to forest resources is essential for the flourishing of FPP, capability creation for FPP requires strong and local social institutions, and FPP's agency (a person's power to act and bring about change) to pursue valued capabilities is often deeply embedded in collective structures. Thus, we developed a framework to guide people‐centered conservation actions that promote the flourishing of FPP. We applied this framework to the Brazilian Caatinga dry forest, which is characterized by diverse use of forest resources and deep social inequities, and identified examples of conservation practices and their mixed influences on the lives of people in this biome. Adopting the CA can help ensure that people‐centered conservation initiatives uphold FPP's rights and prioritize their well‐being, while striving for sustainability.

Evaluation of ceramic and polymeric membranes for crossflow microfiltration of coconut water: Filtration performance and composition of the clarified coconut water - José Diogo da Rocha Viana; Elenilson de Godoy Alves Filho; Lorena Mara Alexandre e Silva; Paulo Riceli Vasconcelos Ribeiro; Carlos Alberto Kenji Taniguchi; Arthur Claudio Rodrigues de Souza; Fernando Antônio Pinto de Abreu; José Carlos Cunha Petrus; Kirley Marques Canuto (Journal of Food Engineering, 2026)

Quantifying variability and viability: A dual-modeling and cytometry approach to Salmonella survival in low-moisture conditions - Mayara M. Oliveira; Arthur Kael Rodrigues da Pia; Syllas B.S. Oliveira; Anderson S. Sant’Ana (Food Control, 2026)

Lupeol as a modulator of bacterial resistance mediated by the MepA efflux pump in Staphylococcus aureus - Nara Juliana Santos Araújo; Camila Aparecida Pereira Silva; Cicera Datiane Morais Oliveira-Tintino; Gabriel Gonçalves Alencar; Maria do Socorro Costa; Ana Raquel Pereira da Silva; Juliete Bezerra Soares; Janaína Esmeraldo Rocha; Saulo Relison Tintino; Vanessa Lima-Bezerra; Henrique Douglas Melo Coutinho; Vanessa Leopoldino Coelho Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Bacterial resistance constitutes one of the main threats to global public health, driving the search for therapeutic strategies capable of restoring the effectiveness of antimicrobials. Among the mechanisms involved, efflux pumps stand out, reducing the intracellular concentration of drugs and contributing to multidrug resistance. In this context, inhibitors of these pumps emerge as a promising approach, as they increase the intracellular concentration of antibiotics. Natural compounds, such as the triterpene lupeol, have been investigated as potential modulators of bacterial resistance due to their relevant biological activities. This study evaluated, from a mechanistic perspective, the ability of lupeol to inhibit the MepA efflux pump in the K2068 strain of Staphylococcus aureus . The minimum inhibitory concentration (MIC) was determined, efflux inhibition assays were performed, membrane permeability analysis was conducted using Sytox Green, ethidium bromide fluorescence was evaluated, RT-qPCR was performed, and molecular docking was performed. The results demonstrated that lupeol exhibits isolated antibacterial activity considered without clinical relevance (MIC ≥ 1024 µg/mL); however, it reduced the MIC of ciprofloxacin and ethidium bromide, indicating inhibition of the MepA pump. No alteration in membrane permeability and an increase in ethidium bromide fluorescence were observed with increasing lupeol concentration. RT-qPCR showed inhibition of mepA gene expression. In molecular docking, the compound presented a binding energy of − 9.01 kcal/mol, with van der Waals, hydrophobic, and hydrogen bonding interactions. It is concluded that lupeol shows potential as an efflux pump inhibitor, acting on the functional inhibition of the pump and the negative regulation of mepA gene expression, thus configuring itself as an adjuvant strategy in combating bacterial resistance.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Distress calls of two species of Pithecopus (Anura, hylidae) in Northeastern Brazil - João Victor Cunegundes de Siqueira; Arthur Felipe Ferreira de Freitas; Daniel Figueiredo de Ramalho; Adsson Rodrigues de Santana; Geraldo Jorge Barbosa de Moura (acta ethologica, 2026)

Impacts of global climate change on nutrition and its effects on neuroeducational outcomes - Ulysses Paulino Albuquerque; Aníbal Silva Cantalice; Washington Soares Ferreira Júnior; Reginaldo Augusto Farias de Gusmão; Arthur Ramalho Magalhães; Flávia Rosa Santoro; Mauro Dias Silva júnior; Wendel J. Teles Pontes; Marco Antonio Correa Varella; Rodrigo Felipe Rodrigues do Carmo (Next Research, 2026)

Small ruminant lentiviruses in dairy goats under tropical conditions: evidence of recombinant genotypes - Nathalie Costa da Cunha; Alana de Oliveira Campello; Leandro dos Santos Machado; Thomas Salles Dias; Thalyta Rodrigues Silva; Arthur de Almeida Figueira; Beatriz Pinheiro Melo da Silva; Lilian Gregory; Barbara Colitti; Dayse Lima da Costa Abreu; Isadora de Fátima Braga Magalhães; Elmiro Rosendo do Nascimento; et al. (Tropical Animal Health and Production, 2026)
Small Ruminant Lentiviruses (SRLVs) are widespread retroviruses of goats and sheep with significant economic and health impacts on small ruminant production systems. This study aimed to investigate the prevalence and genotype distribution of SRLVs in dairy goat flocks from Brazil. A total of 433 blood samples from eight dairy goat farms were analyzed via PCR targeting the gag gene. The overall SRLV prevalence was 32.6%, with marked variation between farms (7.1% to 90.0%). Phylogenetic analysis of 37 selected samples revealed that most sequences clustered within the B1 subtype. Notably, two sequences from farms C and G grouped with subtype A1 and showed evidence of recombination between B1 and A1 strains. These findings provide evidence of recombinant SRLV strains circulating in Brazilian goats. The findings highlight the circulation of distinct and recombinant SRLV strains in the region, reinforcing the importance of continuous molecular surveillance, improved biosecurity practices, and the development of effective control strategies to reduce viral dissemination and mitigate long-term impacts on small ruminant farming.

Thermal and oxidative stress responses of Paecilomyces species recovered from beverage processing environments - Mailah Ali Abdul Rahman Mahfouz; Arthur Kael Rodrigues Pia; Rafaella Santos Mori Bragil; Naara Aparecida Almeida; Anderson S. Sant’Ana; Benedito Corrêa; Rodrigo Savio Pessoa; Liliana de Oliveira Rocha (World Journal of Microbiology and Biotechnology, 2026)

Machine learning for land use change analysis in environmental protection areas - Mayra Vannessa Lizcano Toledo; Johnnatan Rodrigues de Oliveira; Luis Armando De Oro Arenas; Leopoldo André Dutra Lusquinho Filho; Arthur Pereira dos Santos; Raphael de Vicq Ferreira da Costa; Roberto Wagner Lourenço; Darllan Collins da Cunha e Silva (Environmental Monitoring and Assessment, 2026)
Anthropogenic land use and land cover change (LULCC), combined with ongoing climate variability, poses significant challenges to environmental protection areas (EPAs) by altering ecosystem structure, degrading vegetation integrity, and disrupting local climate regulation. Despite their importance, traditional LULCC approaches often fail to incorporate dynamic environmental drivers, limiting their capacity to represent complex landscape-climate interactions. This study investigates the environmental dynamics of the Guaraqueçaba Environmental Protection Area and evaluates the landscape’s potential for automated classification and prediction of impacts associated with land use change. A multitemporal dataset spanning 15 years (2009–2023) was analyzed, comprising an original set of approximately 30.2 million records of annual time series of precipitation, maximum and minimum temperatures, evapotranspiration, global solar radiation, relative humidity, wind speed, land use and land cover information, and the Normalized Difference Vegetation Index (NDVI). To address class imbalance, a balanced subset of 3.6 million records was used for modeling. Predictive models were developed using multiple linear regression (MLR), k -nearest neighbors (KNN), and random forest (RF), with performance assessed under both imbalanced and balanced data conditions using accuracy, $$R^{2}$$ R 2 , precision, recall, and F1-score metrics. The results indicate pronounced local climate changes, including increasing temperatures in anthropogenically modified areas and altered humidity patterns associated with vegetation loss. Among the evaluated models, RF exhibited the highest predictive performance, achieving accuracies of up to 96% and an R $$^{2}$$ 2 of 88.6%, effectively capturing the nonlinear interactions between LULCC, climate variables, and vegetation dynamics. Precipitation and NDVI emerged as the most influential drivers of LULCC processes. These findings demonstrate the effectiveness of machine learning approaches for identifying environmental degradation trajectories in protected areas and provide a robust framework to support targeted mitigation strategies and policy development applicable to other EPAs facing increasing anthropogenic pressure and climate variability.

Microbiological quality of plant-based cheese analogues and pathogen behavior in cashew nut-based varieties - Jaqueline Sousa Correia; Dionisio Pedro Amorim-Neto; Emilie Lang; Matheus Péricles da Silva Láscaris; Beatriz Machado Dal Pian; Larissa Pereira Margalho; Arthur Kael Rodrigues da Pia; Bárbara Cipulo Legabão; Angelica Zaninelli Schreiber; Giulia Paes Strabelo; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2026)

Chemical composition and cooking-induced physicochemical changes in plant-based and meat burgers - Victoria Hermes de Vargas; Arthur Michelon Baldessarelli; Eliseu Rodrigues; Giovana Domeneghini Mercali; Ligia Damasceno Ferreira Marczak (Food Research International, 2026)

Biostimulant Potential of Vitamins in Soybean Cultivation - Vitória Carolina Dantas Alves; Sebastião Ferreira de Lima; Eduardo Pradi Vendruscolo; Travis Wilson Witt; Arthur Renan Fernandes Nogueira; Laura Martins Ferreira; João Flávio Floriano Borges Gomides; Evelyn Rodrigues de Lacerda; Cassio de Castro Seron; Ana Paula Leite de Lima (International Journal of Plant Production, 2026)

Evaluation of the effects of hybrids of metronidazole and eugenol analogues as inhibitors of the Staphylococcus aureus NorA efflux pump: an in vitro and in silico analysis - Lucas dos Santos Sa; João Arthur de Oliveira Borges; Francisco Ruan Moreira da Silva Santos; Cicera Laura Roque Paulo; Daniel Sampaio Alves; Ewerton Yago de Sousa Rodrigues; Ray Silva de Almeida; Sheila Alves Gonçalves; Cícera Datiane de Morais Oliveira Tintino; Lucas Lopardi Franco; Ana Laura Marques Trinca; Douglas Henriques Novais; et al. (Folia Microbiologica, 2026)
Staphylococcus aureus is a Gram-positive coccus-type bacterium responsible for colonizing various sites of the host’s body, thus generating several pathologies such as pneumonia, osteomyelitis, endocarditis, and even cases of sepsis. Eugenol, dihydroeugenol, guaiacol, and phenol are phenolic compounds with antimicrobial activities, as is the drug metronidazole; therefore, eight substances were synthesized by coupling metronidazole with the molecules mentioned above, thus originating the compounds AD1–AD8. The present study aimed to evaluate the antibacterial activity and the capacity of the compounds AD1–AD8 to amplify the action of norfloxacin and ethidium bromide against the S . aureus 1199B strain through the inhibition of the NorA efflux pump. Broth microdilution assays were performed to determine the MIC and to analyze the association of the compounds AD1–AD8 with norfloxacin and ethidium bromide, along with the membrane permeability test and molecular docking. The compounds AD1–AD8 obtained positive results as they exhibited a potentiating effect by reducing the MIC of norfloxacin and ethidium bromide against 1199B, thus evidencing interference with the functioning of the NorA efflux pump, which had already been predicted by the data obtained from the molecular docking assay, in addition to having demonstrated significant effects by acting on the S. aureus membrane. The information obtained from this research is in line with what is reported in the literature regarding the effects observed with eugenol, dihydroeugenol, and guaiacol and their derivatives when combined with other antibiotics against S. aureus strains that possess efflux pumps, with competitive inhibition being observed, as well as the possibility that the reduction in MIC may have occurred due to a reduction in gene expression levels. Further assays are needed to evaluate these possibilities. Based on the presented data, it was found that the compounds AD1–AD8 exhibit promising aspects to act as antibiotic adjuvants.

Nanometer-sized magnetite and its impact on 1H NMR petrophysical characterization of synthetic carbonates - Jonatã Barbosa Teixeira; Gabriella Fazio; Silvia Lorena Bejarano Bermudez; Ângela Leão Andrade; Vitor Emmanuel Paes Silveira; Agide Gimenez Marassi; Mariane Candido; Arthur Gustavo de Araújo Ferreira; José Domingos Fabris; Luiz Carlos Bertolino; Marco Antônio Rodrigues de Ceia; Daniel Ribeiro Franco; et al. (Journal of Applied Geophysics, 2026)

Technological innovation in the production of matured buffalo cheese using artichoke flower extract (Cynara cardunculus L. var. scolymus) as a coagulant: organic acid profile, proteomic and sensory study - Rebeca Rodrigues Vieira Onelli; Josane Cardim de Jesus; Raphael Paturi Lins; Arthur Pompílio da Capela; Leandro Santos Soares; Sibelli Passini Barbosa Ferrão (International Dairy Journal, 2026)

Alkaloid fraction of Duguetia furfuracea demonstrated anti-inflammatory and antinociceptive effects through decrease of tumour necrosis factor alpha in mice models - João Paulo Costa Rodrigues; Fellipe Alexandre Alves Moraes; Flávio Martins de Oliveira; Débora de Oliveira Lopes; Flávia Carmo Horta Pinto; Aline Aparecida Saldanha; Arthur Ladeira Macedo; Carlos Alexandre Carollo; João Máximo de Siqueira; Adriana Cristina Soares (Inflammopharmacology, 2026)

Two species and two karyotypes? Cytogenetic differentiation between Passiflora foetida L. and P. vesicaria L. (Passifloraceae) - Bruna Zirpoli; Arthur Monteiro; Pablo E. Rodriguez; Bruno Leal Viana; Jefferson Rodrigues Maciel; Andrea Pedrosa-Harand; Mariela A. Sader (Systematics and Biodiversity, 2025)

Cashew nut protein concentrate as a potential ingredient for the emerging alternative protein industry - Jéssica Silva do Carmo; José Diogo da Rocha Viana; Arthur Claudio Rodrigues de Souza; Kelvi Wilson Evaristo Miranda; Celli Rodrigues Muniz; Lorena Mara Alexandre e Silva; Matheus Dias de Carvalho; Ana Carla Kawazoe Sato; Daniele Maria Alves Teixeira Sá; Wellington da Silva Oliveira; Fernanda Furlan Gonçalves Dias; Ana Paula Dionísio (Food Chemistry, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Climate change will boost the invasion of the harmful cyanobacterium Raphidiopsis raciborskii in South America - Felipe Morais Zanon; Bruno Henrique Mioto Stabile; Beatriz Melissa Campos; Érica Oliveira de Lima; Matheus Juan Alarcon Sampaio; Yasmin Rodrigues de Souza; Leonardo Rodrigues Tolardo; Mayra Koma Gomes; Luddy Searom Carias de Moraes; Gabriela Sponchiado Hein; Jaqueline Dantas da Silva; Larissa da Silva Pinha; et al. (Harmful Algae, 2025)

Different stocking densities of tilapia fingerlings in BFT system on parameters of water quality and production performance - Sidnei Gregório Tavares; Mariana Lins Rodrigues; Everton Ortiz Rocha; Leonardo Willian de Freitas; Arthur Carniato Sanches; Wilson Rogério Boscolo; Altevir Signor (Aquaculture International, 2025)

Thermophilic dark anaerobic fermentation of glycerol for hydrogen production: Investigating and modelling excess-substrate inhibition - Isabela Mehi Gaspari Augusto; Arthur Gregorio Barbosa Tavares; Armando Zanone; Carolina Zampol Lazaro; Roberta Albanez; José Alberto Domingues Rodrigues; Suzana Maria Ratusznei; Giovanna Lovato (Journal of Environmental Chemical Engineering, 2025)

Effects of the inclusion of a rumen-protected B-vitamin blend and hydroxy trace minerals in the diets of confined Nellore cattle on performance and cecal and ruminal histology - Maria Carolina Gonçalves de Arruda; Rodrigo de Nazaré Santos Torres; Daniela Bernadete Rozza; Luis Arthur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Iasmin Myrele Santos Calaça de Farias; Marco Aurélio Porcionato; Otávio Rodrigues Machado Neto (Animal Feed Science and Technology, 2025)

Plastic dispersion in Northeast Brazil beaches and plastic contaminant detection in Brazilian coast fishing nets - Greici Gubert; Bruna de Ramos; Ronei Cardoso de Oliveira; Karolliny Barbosa de Araújo; Arthur Martins Gabriel; Kátia Alves Ribeiro; Emilly de Souza Cordeiro; Daniele dos Santos Aragão; José Domingos dos Santos Silva; Monica Ferreira da Costa; Emerson Rodrigues de Camargo; Wallace Duarte Fragoso; et al. (Marine Pollution Bulletin, 2025)

How do visitors perceive the urban greenery microclimate in the city’s only green space? A case study in Brazilian semi-arid - Arthur da Silva Nascimento; Leonardo Vitor Alves da Silva; Maria Amanda Nobre Lisboa; Alana de Oliveira Silva; Mardonio Freitas Rodrigues Ferreira; Sara Cardoso Ferreira da Silva; Mário Jorge Vital de Melo; Antônio César Vieira da Silva; João Tavares Calixto Júnior (Environmental Development, 2025)

Interannual variability of upper ocean temperature in the tropical Atlantic: an ocean reanalysis intercomparison - Arthur Prigent; Ingo Richter; Andrea Storto; Riccardo Farneti; Rodrigue Anicet Imbol Koungue; Yuko M. Okumura; Ping Chang (Climate Dynamics, 2025)

Efficacy of Platelet and Leukocyte Rich Fibrin (L-PRF) in the healing process and bone repair in maxillary sinus lift surgeries: a systematic review - Élio Hitoshi Shinohara; Ilan Hudson Gomes de Santana; Mayara Rebeca Martins Viana; Edmundo Junio Rodrigues de Almeida; Anderson Jara Ferreira; José Marcos Pereira Júnior; Arthur Felipe de Brito Andrade; Fernando Kendi Horikawa; Eduardo Dias Ribeiro (Cell and Tissue Banking, 2025)

Discrimination of artisanal Minas cheeses according to geographical origin using spectroscopic and chromatographic techniques associated with chemometrics - Késia Larissa Rodrigues Cardoso; Josane Cardim de Jesus; Adélia Ferreira Dargère; Arthur Pompilio da Capela; Thinara de Freitas Oliveira; Gabriel Ramos Carvalho; Leandro Soares Santos; Peter Bitencourt Faria; Sibelli Passini Barbosa Ferrão (Food Chemistry, 2025)

Biochar amendment as a sustainable alternative to KCl application and its effects on sugarcane physiology and metabolome - Pablo Aislan Freitas e Silva; Mariana Vitória Silvério Alves; Júlia Cristina Amâncio Vieira; Elizabeth Luciana Marinho Miguel; Wisley Moreira Farias; Adriana Barboza Alves; Arthur César Mônico; Elisângela Aparecida da Silva; João Alberto Fischer Filho; Gustavo Henrique Gravatim Costa; Leandro de Souza Pinheiro; Lúcia Pinheiro Santos Pimenta; et al. (Plant Physiology Reports, 2025)

Unraveling niche complementarity and mass ratio hypotheses along Amazon forest succession: Functional composition a key factor for restoration - Jamerson Souza da Costa; Fabrício Alvim Carvalho; Lorena Evangelista Fernandes; Ana Luiza Rangel; Lisandra Mendes Louzada-Camilo; Marcelly de Souza Ventura; Arthur da Cruz Silva; João Augusto Alves Meira-Neto; Andreza Viana Neri; Alex Josélio Pires Coelho; Alice Cristina Rodrigues; Natália Tolêdo Sacchetto; et al. (Acta Oecologica, 2025)

Physicochemical properties, structural analysis and CO2 concentrations of corn grains stored under different conditions - Geraldo Acácio Mabasso; Osvaldo Resende; Diene Gonçalves Souza; Maria Lúcia Ferreira Simeone; Arthur Almeida Rodrigues; Adrielle Borges de Almeida; Jaqueline Ferreira Vieira Bessa; Juliana Aparecida Célia; Valdiney Cambuy Siqueira (Journal of Stored Products Research, 2025)

Acoustic wave propagation in oil wells: A comparison between semi-analytical and finite element modeling approaches - Luis Paulo Brasil de Souza; Juan Andrés Santisteban Hidalgo; Tiago de Magalhães Correia; Isabel Giron Camerini; Guilherme Rezende Bessa Ferreira; Antônio de Souza Rodrigues; Alan Conci Kubrusly; Arthur Martins Barbosa Braga (Wave Motion, 2025)

Cross‐Taxa Analysis of Long‐Term Data Reveals a Positive Biodiversity‐Stability Relationship With Taxon‐Specific Mechanistic Underpinning - Arthur V. Rodrigues; Tuuli Rissanen; Mirkka M. Jones; Ida‐Maria Huikkonen; Otso Huitu; Erkki Korpimäki; Mikko Kuussaari; Aleksi Lehikoinen; Andreas Lindén; Hannu Pietiäinen; Juha Pöyry; Pasi Sihvonen; et al. (Ecology Letters, 2025)
Anthropogenic environmental change is altering biodiversity at unprecedented rates, threatening the stability of ecosystem services on which humans depend. However, most of what is known about biodiversity–stability relationships comes from experimental studies making extrapolation to real ecosystems difficult. Here, we ask whether the shape and underlying mechanisms of the biodiversity–stability relationship vary among taxa in real‐world communities. Our study harnesses the power of six terrestrial and aquatic long‐term monitoring datasets, encompassing entire assemblages at hundreds of georeferenced sites providing 20 years long community measurements, covering a 1200 km latitudinal gradient across Finland. In general, we detect a positive relationship between species richness and stability. Structural equation modelling reveals that this relationship is modified by functional trait community composition, with specific mechanisms varying among the taxa. Our study is among the first to highlight the importance of functional traits in elucidating both general and taxon‐specific impacts of biodiversity on community stability.

What is the Major Cause of Pinus taeda Nutritional Disorder in Southern Brazil? - Valdécio dos Santos Rodrigues; Antônio Carlos Vargas Motta; João Bosco Vasconcellos Gomes; Itamar Antonio Bognola; Ederlan Magri; Stephen Arthur Prior; Sérgio Ricardo Silva; Celso Garcia Auer; Shizuo Maeda; Mauro Murara Junior (Journal of Soil Science and Plant Nutrition, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Fuzzy inference algorithm for quantifying thermal comfort in peri-urban environments - Rodrigo Couto Santos; Ricardo Baréa; Arthur Carniato Sanches; Raimundo Rodrigues Gomes Filho; Sivanilza Teixeira Machado; Jhon Lennon Bezerra da Silva; André Luiz Nascimento Lopes; Marcos Vinícius da Silva (Environment, Development and Sustainability, 2024)

Ultrasound technology supplements zinc in soybean seeds and increases the photosynthetic efficiency of seedlings - Érica Souza Gomes; Gustavo Roberto Fonseca de Oliveira; Arthur Almeida Rodrigues; Camila Graziela Corrêa; Eduardo de Almeida; Hudson Wallace Pereira de Carvalho; Valter Arthur; Edvaldo Aparecido Amaral da Silva; Arthur I. Novikov; Clíssia Barboza Mastrangelo (Computers and Electronics in Agriculture, 2024)

Mathematical modeling for the prediction of biofilm formation and removal in the food industry as strategy to control microbiological resistance - Camila Rodrigues Carneiro; Nathália Nogueira Leite; Arthur Vinicius de Abreu Oliveira; Marquejon dos Santos Oliveira; Daiana Wischral; Monique Renon Eller; Solimar Gonçalves Machado; Eduardo Basílio de Oliveira; Wilmer Edgard Luera Pena (Food Research International, 2024)

Enhancement of phenolic compounds bioaccessibility in jabuticaba wine through fermentation by Saccharomyces cerevisiae - Larissa Lorrane Rodrigues Borges; Valdeir Viana Freitas; Amanda Lais Alves Almeida Nascimento; Janaina Gonçalves Fernandes; Hélia de Barros Kobi; Monique Renon Eller; Frederico Augusto Ribeiro de Barros; Luciana Ângelo de Souza; Gabriel Abranches Dias Castro; Arthur Figueira de Carvalho; Jaqueline de Araújo Bezerra; Sergio Antonio Fernandes; et al. (Food and Bioproducts Processing, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Comprehensive dynamics of bacterial and fungal diversity throughout concentrated chicken broth processing: Integrating culture-dependent and independent techniques - José T.D. Rodrigues; Larissa P. Margalho; Arthur K.R. Pia; Héctor Sierra; Louise Tavares; Míriam G. Marquezini; Melline Fontes Noronha; Lucélia Cabral; Wilson José Fernandes Lemos Junior; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

VARI as an indicator of site productivity of Pinus taeda L.: soil, litter, and plant nutrition - Tamires Maiara Ercole; João Bosco Vasconcellos Gomes; Valdécio dos Santos Rodrigues; Nicolas dos Santos Trentin; Jairo Calderari de Oliveira Junior; Gabriel Assis-Pereira; Mario Tomazello-Filho; Amanda Pacheco Cardoso Moura; Shizuo Maeda; Stephen Arthur Prior; Rangel Consalter; Antônio Carlos Vargas Motta (European Journal of Forest Research, 2024)

Neurological aspects of HTLV-1 infection: symptoms in apparently asymptomatic carriers - Qesya Rodrigues Ferreira; Ana Flávia Novaes; Carolina Souza Santana; Arthur Shigueru Umeda; Jéssica Oliveira de Souza Nascimento; João Pedro Melo de Freitas Santos; Larissa Alves Fernandes; Matheus Nascimento Moura; Rebeca Leão Amorim; Vinícius Nogueira Cavalcanti; Ariana Leal Borges da Cruz; Fernanda Khouri Barreto; et al. (Journal of NeuroVirology, 2024)

Organ-specific proteomes of Selaginella convoluta provide insights into its desiccation tolerance mechanisms - Fernanda Priscila Santos Reginaldo; Luiz Fernando Rodrigues de Souza; Daisy Sotero Chacon; Marlon Dias Mariano Santos; Taffarel Melo Torres; Ivanice Bezerra da Silva; Alan de Araújo Roque; Carlos André O. Ricart; Mariana S. Castro; Paulo Costa Carvalho; Wagner Fontes; Marcelo Valle de Sousa; et al. (Plant Biosystems, 2024)

Innovative pathways for ethanol production: Harnessing xylose’s bioenergy potential using Brazilian wild isolated yeasts - Marcus Vinicius Astolfo da Costa; Ana Carolina Rodrigues Sousa; Arthur Gasseta Batista; Fernanda Elisa Gomes Miranda Paula; Marita Vedovelli Cardozo; Sarah Regina Vargas; Rafael Rodrigues Philippini; Caio Roberto Soares Bragança (Bioresource Technology, 2024)

Efficacy and safety of guttiferone E in melanoma-bearing mice - Arthur Barcelos Ribeiro; Matheus Reis Santos de Melo; Marcela de Melo Junqueira; Mônica Garcia Leal Rodrigues; Thiago Olimpio de Souza; Gabriela Fernandes; Mário Ferreira Conceição Santos; Sérgio Ricardo Ambrósio; Jairo Kenupp Bastos; Denise Crispim Tavares (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Mapping species richness and evolutionary regions of the genus Myrcia - Arthur Vinicius Rodrigues; Leandro Duarte (Journal of Biogeography, 2024)
Aim Myrcia is a plant genus exclusive of the Neotropical region and one of the most important components of the tree diversity in the Cerrado and Atlantic Forest domains. However, no mapping of its taxonomic diversity for this region exists. Our aim was to describe the spatial patterns of diversity and biogeographical history for Myrcia in the Neotropical region based on a phylogenetic regionalization. Location Neotropics. Taxon Genus Myrcia (Myrtaceae). Methods We derived distributions for 307 species from occurrence records using buffering and species distribution modelling. We used stacked distributions to generate a richness map of the genus and its clades (sections). In addition, we used phylogenetic regionalization methods to define evolutionary regions (evoregions) and ancestral area reconstruction to reveal the biogeographical history across these evoregions. Results We found high species richness in the Atlantic Forest and Cerrado, with some sections restricted to the East coast of South America, while others were widespread across the Neotropics. We defined five evoregions, named A–E; the ancestral reconstruction revealed that Myrcia originated in evoregion B, under a tropical climate, with further specialization of distant‐related lineages to the colder environmental condition in evoregion A. Main Conclusions High species richness of Myrcia in South America eastern coast and in the Brazilian highlands coincides with the evoregions with most diversification. Our genus‐specific regionalization together with the ancestral area reconstruction showed that evoregions A and B were the main evolutionary regions where diversification took place. In addition, the biogeographical history of the group suggests that some lineages have adaptations to deal with colder environments, that probably evolved in response to cooling periods since the mid‐Miocene.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Functional genes related to N and P cycling in degraded and restored areas from Brazilian drylands - Danilo F. Silva; Elke J.B.N. Cardoso; Laibin Huang; Christian Erikson; Antonio M.M. Silva; Victor L.V.P. Araujo; Davila E.O. Silva; Vania M.M. Melo; Ademir S.F. Araujo; Arthur P.A. Pereira; Jorge L. Mazza Rodrigues (Applied Soil Ecology, 2024)

Herodotools: An R package to integrate macroevolution, biogeography and community ecology - Gabriel Nakamura; Arthur V. Rodrigues; André Luís Luza; Renan Maestri; Vanderlei Debastiani; Leandro Duarte (Journal of Biogeography, 2024)
Aim Speciation, extinction and historical dispersal are the ultimate factors generating and maintaining biodiversity. However, methods of macroevolution used to detect historical processes usually ignore the variation of macroevolutionary processes at scales finer than entire regions. Likewise, biogeography and community ecology often ignore deep‐time evolutionary processes. To overcome this problem, it is necessary to integrate data from ancestral state reconstructions, current species distributions and biogeographical regionalization. Herodotools is an R package designed to perform this integration. Location Global application, with an example from Neotropics. Major taxa studied Any taxa, with an example from small rodents (genus Akodon and subfamily Sigmodontinae). Methods Herodotools streamline analyses of historical biogeography, including regionalization, calculation of assemblage age, lineage in situ diversification and community phylogenetic metrics, merging species occurrence with macroevolutionary methods of ancestral area and trait reconstruction. The main functions of our R package are presented with toy examples and by analysing the historical biogeography of small rodent assemblages in the Neotropics. Results Our package can integrate methods from biogeography, macroevolution and community ecology, allowing us to downscale the effects of historical processes and calculate important historical variables (e.g., age of assemblages, in situ diversification, phylogenetic regionalization, phylogenetic transition zones, metrics of trait macroevolutionary dynamics and new metrics of phylogenetic diversity and endemism) in different scales, from entire regions to communities of co‐occurrent species. Main Conclusions Herodotools is the first platform to streamline the analysis of historical biogeography, enabling a better understanding of historical processes at different levels of organization, from local assemblages to entire biogeographical regions and incorporating macroevolutionary models in commonly used community phylogenetic metrics. This integration bridges the gap between macroevolutionary, biogeography and community ecology methods.

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

Doxycycline treatment modulates the immune response of tilapia and controls Aeromonas hydrophila infection - Susana Luporini de Oliveira; Camila Carlino da Costa; Mayumi Fernanda Aracati; Leticia Franchin Rodrigues; Hélio José Montassier; Gabriel Conde; Romário Alves Rodrigues; Ives Charlie-Silva; Patrícia Bianca Clissa; Luiz Arthur Malta Pereira; Marco Antonio de Andrade Belo (Aquaculture, 2024)

Anaerobic digestion of crude glycerol from biodiesel production for biogas generation: Process optimization and pilot scale operation - Bruna Sampaio de Mello; Arthur Pozzi; Brenda Clara Gomes Rodrigues; Maria Angélica Martins Costa; Arnaldo Sarti (Environmental Research, 2024)

Future weakening of southeastern tropical Atlantic Ocean interannual sea surface temperature variability in a global climate model - Arthur Prigent; Rodrigue Anicet Imbol Koungue; Joke F. Lübbecke; Peter Brandt; Jan Harlaß; Mojib Latif (Climate Dynamics, 2024)
Future changes in the southeastern tropical Atlantic interannual sea surface temperature (SST) variability in response to increasing greenhouse gas concentrations are investigated utilizing the global climate model FOCI. In that model, the Coastal Angola Benguela Area (CABA) is among the regions of the tropical Atlantic that exhibits the largest surface warming. Under the worst-case scenario of the Shared Socioeconomic Pathway 5-8.5 (SSP5-8.5), the SST variability in the CABA decreases by about 19% in 2070–2099 relative to 1981–2010 during the model’s peak interannual variability season May–June–July (MJJ). The weakening of the MJJ interannual temperature variability spans the upper 40 m of the ocean along the Angolan and Namibian coasts. The reduction in variability appears to be related to a diminished surface-layer temperature response to thermocline-depth variations, i.e., a weaker thermocline feedback, which is linked to changes in the mean vertical temperature gradient. Despite improvements made by embedding a high-resolution nest in the ocean a significant SST bias remains, which might have implications for the results.

First report of feeding injury of Proba fraudulenta Stäl (Hemiptera: Miridae) to Cynara cardunculus (L.) Fiori (Asterales: Asteraceae) in Brazil - Maria Luiza Mimbú Osako; Paulo Sergio Fiuza Ferreira; Luciano Santana Fiuza Ferreira; Guilherme Rodrigues Tomé; Flávio Gabriel Bianchini; Arthur Vieira Ribeiro; Cristina Schetino Bastos; Ricardo Siqueira da Silva; Tamíris Alves de Araújo (Crop Protection, 2024)

Physiological performance of brassinolide-conditioned green soybean seeds - Thaís Fernandes de Jesus; Arthur Almeida Rodrigues; Layane Soares do Santos; Adinan Alves da Silva; Alan Carlos da Costa; Juliana de Fátima Sales (South African Journal of Botany, 2024)

Environmental monitoring of SARS-CoV-2 in the metropolitan area of Porto Alegre, Rio Grande do Sul (RS), Brazil - Leticia Batista Dutra; Janaína Francieli Stein; Bruna Seixas da Rocha; Andresa Berger; Beatriz Andrade de Souza; Bruno Aschidamini Prandi; Arthur Tonietto Mangini; André Jarenkow; Aline Alves Scarpellini Campos; Fernando Mainardi Fan; Maria Cristina de Almeida Silva; Katia Helena Lipp-Nissinen; et al. (Environmental Science and Pollution Research, 2023)
Since starts the coronavirus disease 2019 (COVID-19) pandemic identified the presence of genomic fragments of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in various environmental matrices: domestic sewage, surface waters, and contaminated freshwater. Environmental monitoring of SARS-CoV-2 is a tool for evaluating trend curves over the months, compared to several clinical cases of the disease. The objective of this study was to monitor the SARS-CoV-2 in environmental samples collected in different sites in a metropolitan area of Porto Alegre, Southern Brazil. During 10 months from 2020 to 2021, 300 samples were collected weekly and biweekly from nine points located in 3 cities: one point from a wastewater treatment plant (WWTP) in São Leopoldo (fortnightly collection), two points in Dilúvio Stream in Porto Alegre (fortnightly collection), two points in Pampa and Luiz Rau Streams (weekly collection), and two points in public fountains (fortnightly collection) in Novo Hamburgo. After collection, samples were concentrated by ultracentrifugation, and viral nucleic acids were extracted using MagMax® Core Nucleic Acid Purifications kits and submitted to RT-qPCR, using E, N1, and N2 gene targets of SARS-CoV-2. Only 7% (3/41) samples from public fountains were positive, with a mean viral load (VL) of SARS-CoV-2 RNA of 5.02 × 10 1 gc/l (2.41~8.59 × 10 1 gc/l), while the streams had average VL of 7.43 × 10 5 gc/l (Pampa), 7.06 × 10 5 gc/l (Luiz Rau), 2.01 × 10 5 gc/l (Dilúvio), and 4.46 × 10 5 cg/l (WWTP). The results showed varying levels of viral presence in different sample types, with a demonstrated correlation between environmental viral load and clinical COVID-19 cases. These findings contribute to understanding virus persistence and transmission pathways in the environment. Continuous monitoring, especially in less developed regions, is crucial for early detection of vaccine resistance, new variants, and potential COVID-19 resurgence.

Oil spill environmental sensitivity mapping of Rio de Janeiro, Brazil - Flávio Henrique Rodrigues; André de Andrade Kolya; Vinicius Mendes Veiga; Sara Felix dos Santos; Arthur Wieczorek; Claudia Vanessa dos Santos Corrêa; Daiana Marques Costa; Lucília do Carmo Giordano; Paulina Setti Riedel; Fábio A.G.V. Reis (Marine Pollution Bulletin, 2023)

Solar photocatalysis using post-consumer alkaline batteries for degrading contaminants of emerging concern in surface water - Guenther Carlos C. Viana; Elisângela Maria R. Rocha; Elisandra Scapin; Arthur Cahino; Iris Rebeca D. Leite; Daniel A. Bertuol; José D. Ardisson; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Sex distinctions regarding serum zinc levels in critically ill COVID-19 patients - Cristina Gama Matos Pereira; Marco Antônio Prado Nunes; Arthur Leite Lessa; Lara Carvalho Cerqueira; Octavio Morais Veloso; Felipe Mendes Delpino; Andrêa Ferreira; Fernanda Noronha de Góis; Patrícia Santos Rodrigues Costa; Heitor Oliveira Santos (Journal of Trace Elements in Medicine and Biology, 2023)

Biochar as a carbonaceous material to enhance soil quality in drylands ecosystems: A review - Ícaro Vasconcelos do Nascimento; Laís Gomes Fregolente; Arthur Prudêncio de Araújo Pereira; Carla Danielle Vasconcelos do Nascimento; Jaedson Cláudio Anunciato Mota; Odair Pastor Ferreira; Helon Hébano de Freitas Sousa; Débora Gonçala Gomes da Silva; Lucas Rodrigues Simões; A.G. Souza Filho; Mirian Cristina Gomes Costa (Environmental Research, 2023)

Spatial distribution of the greater rhea, Rhea americana (Linnaeus, 1758), in Rio Grande do Sul, southern Brazil: citizen-science data, probabilistic mapping, and comparison with expert knowledge - André L. Luza; Arthur V. Rodrigues; Louisa Mamalis; Viviane Zulian (Ornithology Research, 2023)

Trend analysis and identification of possible periods of change in the occurrence of extreme streamflow events in a tropical basin - Carla Larissa Fonseca da Silva; Demetrius David da Silva; Michel Castro Moreira; Jackson Martins Rodrigues; Igor Steven de Sousa Rocha; Rafael Petruceli Coelho Lima; Arthur Telles Calegario (Journal of South American Earth Sciences, 2023)

Environmental sensitivity index maps to manage oil spill risks: A review and perspectives - Fernando Mazo D'Affonseca; Fábio Augusto Gomes Vieira Reis; Claudia Vanessa dos Santos Corrêa; Arthur Wieczorek; Lucilia do Carmo Giordano; Mara Lúcia Marques; Flávio Henrique Rodrigues; Daiana Marques Costa; André de Andrade Kolya; Vinicius Mendes Veiga; Sarah Félix Santos; Laila Milani Magalhães; et al. (Ocean & Coastal Management, 2023)

Phytochemical analysis, in vitro antioxidant and anticholinesterase activities of Solanum paniculatum L. and an in-silico test with the AChE enzyme - João Paulo Rodrigues da Silva; Adriane da Cunha Rios Aragão; Ronaldo dos Santos Sousa Junior; Clara Andrezza Crisóstomo Bezerra Costa; Orlando Francisco da Silva Moura; Thaís Danyelle Santos Araújo; Durcilene Alves da Silva; Antonio Rodrigues da Silva Neto; Kessia da Costa Silva; Tatiana de Oliveira Lopes; Penina Sousa Mourão; Lorena Thayla Nascimento e Sousa; et al. (South African Journal of Botany, 2023)

From wasted ferric sludge to valuable waste: a systematic review using the knowledge development process—constructivist method - Iana Chaiene de Araujo Vidal; Elisângela Maria Rodrigues Rocha; Arthur Marinho Cahino; Samara Teixeira Pereira; Amanda Gondim Cabral Quirino; Raqueline Caldas do Nascimento (Environment, Development and Sustainability, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

N-acetylation of toxic aromatic amines by fungi: Strain screening, cytotoxicity and genotoxicity evaluation, and application in bioremediation of 3,4-dichloroaniline - Amanda Dal’Ongaro Rodrigues; Arthur dos Santos Montanholi; Angela Akimi Shimabukuro; Murilo Kioshi Aquino Yonekawa; Nadla Soares Cassemiro; Denise Brentan Silva; Clarice Rossato Marchetti; Carlos Eduardo Weirich; Adilson Beatriz; Fabiana Fonseca Zanoelo; Maria Rita Marques; Giovana Cristina Giannesi; et al. (Journal of Hazardous Materials, 2023)

Use of oral fluid samples for the investigation of outbreaks of human parvovirus B19 infection - Daiana Lima Almada; Arthur Daniel Rocha Alves; Luciane Almeida Amado Leon; Débora Familiar Rodrigues Macedo; Solange Artimos de Oliveira; Marilda Mendonça Siqueira; David Brown; Rita de Cássia Nasser Cubel Garcia (Brazilian Journal of Microbiology, 2022)

Tolerance and reduction of chromium by bacterial strains - Sandra Mara Barbosa Rocha; Marineide Rodrigues do Amorim; Mayanna Karlla Lima Costa; Tályta Carine da Silva Saraiva; Romário Martins Costa; Jadson Emanuel Lopes Antunes; Louise Melo de Souza Oliveira; Francisco de Alcantara Neto; Erika Valente de Medeiros; Arthur Prudencio de Araujo Pereira; Ademir Sergio Ferreira Araujo (Archives of Microbiology, 2022)

Effect of dietary inclusion of licuri cake on intake, feeding behavior, and performance of feedlot cull cows - Maria Luíza França Silva; Gleidson Giordano Pinto de Carvalho; Fabiano Ferreira da Silva; Laize Vieira Santos; Marceliana da Conceição Santos; Ana Paula Gomes da Silva; Arthur Santos Danieleto; Talia da Cruz Silva Mandinga; Tarcísio Ribeiro Paixão; Dorgival Morais de Lima Júnior; Robério Rodrigues Silva (Tropical Animal Health and Production, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The 2019 Benguela Niño - Rodrigue Anicet Imbol Koungue; Peter Brandt; Joke Lübbecke; Arthur Prigent; Meike Sena Martins; Regina R. Rodrigues (Frontiers in Marine Science, 2021)
High interannual sea surface temperature anomalies of more than 2°C were recorded along the coasts of Angola and Namibia between October 2019 and January 2020. This extreme coastal warm event that has been classified as a Benguela Niño, reached its peak amplitude in November 2019 in the Angola Benguela front region. In contrast to classical Benguela Niños, the 2019 Benguela Niño was generated by a combination of local and remote forcing. In September 2019, a local warming was triggered by positive anomalies of near coastal wind-stress curl leading to downwelling anomalies through Ekman dynamics off Southern Angola and by anomalously weak winds reducing the latent heat loss by the ocean south of 15°S. In addition, downwelling coastal trapped waves were observed along the African coast between mid-October 2019 and early January 2020. Those coastal trapped waves might have partly emanated from the equatorial Atlantic as westerly wind anomalies were observed in the central and eastern equatorial Atlantic between end of September to early December 2019. Additional forcing for the downwelling coastal trapped waves likely resulted from an observed weakening of the prevailing coastal southerly winds along the Angolan coast north of 15°S between October 2019 and mid-February 2020. During the peak of the event, latent heat flux damped the sea surface temperature anomalies mostly in the Angola Benguela front region. In the eastern equatorial Atlantic, relaxation of cross-equatorial southerly winds might have contributed to the equatorial warming in November 2019 during the peak of the 2019 Benguela Niño. Moreover, for the first time, moored velocities off Angola (11°S) revealed a coherent poleward flow in the upper 100 m in October and November 2019 suggesting a contribution of meridional heat advection to the near-surface warming during the early stages of the Benguela Niño. During the Benguela Niño, a reduction of net primary production in the Southern Angola and Angola Benguela front regions was observed.

Dynamics of bacterial and archaeal communities along the composting of tannery sludge - Ademir Sergio Ferreira Araujo; Arthur Prudêncio de Araujo de Pereira; Jadson Emanuel Lopes Antunes; Louise Melo de Souza Oliveira; Wanderley José de Melo; Sandra Mara Barbosa Rocha; Marineide Rodrigues do Amorim; Fabio Fernando Araujo; Vania Maria Maciel Melo; Lucas William Mendes (Environmental Science and Pollution Research, 2021)

Proteome of Erythroxylum pungens (Erythroxylaceae): an endemic species of the semiarid Caatinga - Daisy Sotero Chacon; Ivanice Bezerra da Silva; Taffarel Melo Torres; Gabrielle Macedo Pereira; Letícia Gondim Lambert Moreira; Luiz Fernando Rodrigues de Souza; Fernanda Priscila Santos Reginaldo; Alan de Araújo Roque; José Angelo S. Zuanazzi; Renata Libonati; Julia A. Rodrigues; Filippe L.M Santos; et al. (Plant Biosystems, 2021)

Floral glands in myophilous and sapromyophilous species of Pleurothallidinae (Epidendroideae, Orchidaceae)—osmophores, nectaries, and a unique sticky gland - Gustavo Arévalo-Rodrigues; Fábio de Barros; Arthur R. Davis; Poliana Cardoso-Gustavson (Protoplasma, 2021)

Pesticide and trace element bioaccumulation in wild owls in Brazil - Gabriela Elisa Dal Pizzol; Vitória Aquino Rosano; Elinton Rezende; Jonas Claudiomar Kilpp; Marcelo Menezes Ferretto; Enzo Mistura; Arthur Nery da Silva; Charise Dallazem Bertol; Laura Beatriz Rodrigues; Maria Tereza Friedrich; Luciana Grazziotin Rossato-Grando (Environmental Science and Pollution Research, 2021)

A multivariate approach to the physical and physiological quality of hybrid corn seeds affected by Molicutes and MRFV - Jhonata Cantuária Medeiros; Juliana de Fátima Sales; Jacson Zuchi; Kelly Juliane Teles Nascimento; Fernando Higino de Lima e Silva; Stella Tomaz de Castro; Adriano Carvalho Costa; Arthur Almeida Rodrigues (Euphytica, 2021)

Citrus Mealybug Performance and Plant Strata Preference on Different Coffee Varieties - Nilson Rodrigues-Silva; Gerson Adriano Silva; Pablo Costa Gontijo; Tarcísio Vinsintin da Silva Galdino; Arthur Vieira Ribeiro; Marcelo Coutinho Picanço (Neotropical Entomology, 2021)

The latex of Euphorbia tirucalli inhibits staphyloxanthin production and protects Tenebrio molitor larvae against Staphylococcus aureus infection - Arthur Henrique Mendes Colasso; Thayná Fernandes Barros; Isabella Fernandes da Silva Figueiredo; Alexsander Rodrigues Carvalho Junior; Elizabeth Soares Fernandes; Michelle Russo Bendelak Uchoa; Luís Cláudio Nascimento da Silva (Natural Product Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Anti-Melanoma Activity of Indomethacin Incorporated into Mesoporous Silica Nanoparticles - Natália Helen Ferreira; Arthur Barcelos Ribeiro; Francisco Rinaldi-Neto; Fernanda Santos Fernandes; Samuel do Nascimento; Wilson Rodrigues Braz; Eduardo José Nassar; Denise Crispim Tavares (Pharmaceutical Research, 2020)

Tolerance of Hancornia speciosa Gomes (Apocynaceae) to potassium fluoride: physiological and anatomical traits - Thaís Andrade de Carvalho Silva; Sebastião Carvalho Vasconcelos-Filho; Arthur Almeida Rodrigues; Douglas Almeida Rodrigues; Luciana Minervina de Freitas Moura; Izadora Andrade Gonçalves; Alan Carlos Costa; Efraim Lázaro Reis; Leandro Carlos; Caroline Müller (Acta Physiologiae Plantarum, 2020)

Global rheophytes data set: angiosperms and gymnosperms - Laís Mara Santana Costa; Márcia Goetze; Arthur Vinícius Rodrigues; Guilherme Dubal dos Santos Seger; Fernanda Bered (Ecology, 2020)
The term rheophyte describes a biological group of flood‐tolerant plants that are confined to the beds of swift‐running streams and rivers in nature and grow up to flood level, but not beyond the reach of regularly occurring flash floods. Although over 35 yr have passed since the first global census of rheophytes, no updates have been recorded regarding the number of taxa in this biological group in seed plants. Therefore, the present work aimed to (1) review the main topics associated with rheophytism (e.g., morphological characteristics, genetic studies, geographic distribution, conservation, and evolutionary aspects); (2) provide an updated checklist of rheophytes distributed around the world considering the two main groups in seed plants (gymnosperms and angiosperms); (3) demonstrate the distribution of rheophytism in the angiosperm phylogeny; and (4) estimate the geographical distribution and richness of selected taxa on the world map for the first time. All data compiled for the present study originated from a search of peer‐reviewed articles, secondary literature (theses, dissertations, reports, books, and floras), and electronic facilities. We compiled a data set composed of four taxa in gymnosperms (Podocarpaceae family) and 1,368 taxa (including obligate, facultative, and unclassified rheophytes) distributed in 114 families and 508 genera in angiosperms. Most of the studied taxa belong to eudicotyledons (72.81%), while 1.46% belong to magnoliids, and 25.73% belong to monocotyledons. The families with the highest number of taxa in descending order are Podostemaceae, Araceae, Myrtaceae, Rubiaceae, Asteraceae, Apocynaceae, Arecaceae, Fabaceae, Phyllanthaceae, and Poaceae. Of the 114 families plotted in angiosperm phylogeny, at least 80 harbor obligate rheophytes. The geographical distribution of rheophytes in angiosperms, as expected based on the first census of this biological group, is mainly in the tropical and subtropical regions. The high richness of rheophytic taxa was mostly found in southern Mexico, southern China, Borneo, and northern and eastern Australia. In contrast, the geographical distribution of rheophytes in gymnosperms is restricted to New Caledonia and Tasmania. The present study will help to advance knowledge regarding the diversity of rheophytes in angiosperms and gymnosperms while drawing attention to this biological group, which has often been overlooked. There are no copyright restrictions. Please cite this data paper when the data are used in publications and teaching events.

Semi-Automatic Identification of Submarine Pipelines with Synthetic Aperture Sonar Images - Victor Hugo Fernandes; Nilcilene das Graças Medeiros; Dalto Domingues Rodrigues; Arthur Ayres Neto; Júlio César de Oliveira (Marine Geodesy, 2020)

Proteomic profiles during adventitious rooting of Eucalyptus species relevant to the cellulose industry - Márcia Rodrigues de Almeida; Joséli Schwambach; Vanildo Silveira; Angelo Schuabb Heringer; Janette Palma Fett; Arthur G. Fett-Neto (New Forests, 2020)

Potential of calcium nitrate to mitigate the aluminum toxicity in Phaseolus vulgaris: effects on morphoanatomical traits, mineral nutrition and photosynthesis - Camila Vilela Vasconcelos; Alan Carlos Costa; Caroline Müller; Gustavo Castoldi; Andréia Mendes Costa; Kássia de Paula Barbosa; Arthur Almeida Rodrigues; Adinan Alves da Silva (Ecotoxicology, 2020)

Ricinus communis as a phytoremediator of soil mineral oil: morphoanatomical and physiological traits - Larissa Saeki Rehn; Arthur Almeida Rodrigues; Sebastião Carvalho Vasconcelos-Filho; Douglas Almeida Rodrigues; Luciana Minervina de Freitas Moura; Alan Carlos Costa; Leandro Carlos; Juliana de Fátima Sales; Jacson Zuchi; Lucas Peres Angelini; Fernando Higino de Lima Silva; Caroline Müller (Ecotoxicology, 2020)

Modelling changes in forest attributes driven by human activities at different spatial scales in the subtropical Atlantic Forest - Débora Vanessa Lingner; Arthur Vinicius Rodrigues; Laio Zimermann Oliveira; André Luís de Gasper; Alexander Christian Vibrans (Biodiversity and Conservation, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

How deep can ectomycorrhizas go? A case study on Pisolithus down to 4 meters in a Brazilian eucalypt plantation - Agnès Robin; Céline Pradier; Hervé Sanguin; Frédéric Mahé; George Rodrigues Lambais; Arthur Prudêncio de Araujo Pereira; Amandine Germon; Maiele Cintra Santana; Pierre Tisseyre; Anne-Laure Pablo; Pauline Heuillard; Marie Sauvadet; et al. (Mycorrhiza, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Erratum to: Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Indomethacin treatment reduces microglia activation and increases numbers of neuroblasts in the subventricular zone and ischaemic striatum after focal ischaemia - Rosana S Lopes; Marcelo M Cardoso; Arthur O Sampaio; Mario Santos Barbosa; Celice C Souza; Michelle C da Silva; Elane Magno N Ferreira; Marco Aurelio M Freire; Rafael Rodrigues Lima; Walace Gomes-Leal (Journal of Biosciences, 2016)

Taxonomic status and origin of the Egyptian weasel (Mustela subpalmata) inferred from mitochondrial DNA - Mónica Rodrigues; Arthur R. Bos; Richard Hoath; Patrick J. Schembri; Petros Lymberakis; Michele Cento; Wissem Ghawar; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Genetica, 2016)

A set of standard area diagrams to assess severity of frogeye leaf spot on soybean - Daniel Debona; Kelly Juliane Telles Nascimento; Danielle Rezende; Jonas Alberto Rios; Arthur Martins Almeida Bernardeli; Leandro Castro Silva; Fabrício Ávila Rodrigues (European Journal of Plant Pathology, 2015)

Adventitious rooting of Eucalyptus globulus × maidennii mini-cuttings derived from mini-stumps grown in sand bed and intermittent flooding trays: a comparative study - Joséli Schwambach; Carolina Michels Ruedell; Márcia Rodrigues de Almeida; Ricardo Miguel Penchel; Elias Frank de Araújo; Arthur G. Fett-Neto (New Forests, 2008)